The influence of fitness content creators on women’s personal image formation and their pursuit of healthy lifestyle habits: A literature review (Research, Society and Development, 2025)
This study examines the influence of social media on women’s body image formation and adoption of healthy habits, with particular emphasis on the role of fitness digital influencers. It discusses how media and online content shape perceptions of diet, exercise, and the body, as well as the need for critical literacy when consuming health information disseminated on these platforms. The study contextualizes the importance of understanding this influence given the increasing reliance on social networks for guidance on healthy behaviors and the potential risks of internalizing standards that are not evidence-based. In this context, the objective was to identify the influence of fitness influencers on women’s personal image construction and their pursuit of healthy lifestyle habits. A literature review was conducted using databases such as PubMed®, SciELO, and LILACS. Five relevant studies were identified (n = 844 participants). The findings indicate a significant impact of social media on eating behaviors, self-image, and mental health, with a high prevalence of influencers serving as a primary source of dietary advice. Concerns emerge regarding credibility, lack of professional guidance, and the need for digital health education strategies. The review highlights the need for more robust methodologies, better control of confounding variables, and longitudinal approaches to clarify causal relationships between social media use, beauty standards, psychological well-being, and health.